Coronary heart disease risk factors : prevalence among the female Malay USM staffs - Rashid, Nikarmiza Mat (2005)
Cardiovascular disease is progressively becoming a major cause of morbidity and mortality in women generally after menopause. In this study, our aim was to detect the prevalence of risk factors for coronary heart disease (CHD) among Malay female USM staffs aged 30 or over and to inform individual presenting with coronary heart disease. We examined the risk factors for CHD, which includes high blood pressure, high blood cholesterol, hypertension, diabetes, and higher body mass index, which are common in women. The blood samples was analyzed and questionnaire was given out to the Malay female staff in USM from December 2004 to March 2005. Distribution of subjects according to staff categories is 30o/o academic and 70o/o non-academic staff. From the data analysis, 62.5% of the subjects do the physical activity more than 1 hour however 68o/o of there are obese, 25% with hypertension, 43.8% suffering from hypercholesterolemia and 12.5% having high blood glucose. In this study, we can conclude that there is no significant difference between active and passive subjects to CHD. Therefore, we would like to mention that in addition to the primary prevention and early detection of CHD, the compliance of patients with their treatment should be the focus of clinicians in order to minimize CHD morbidity and mortality.